STUDY ON MODIFICATION OF NANO ZIRCONIUM OXIDE WITH POLYDIMETHYL SILOXANE - Ngọc (Journal of Military Science and Technology, 2021)
Nano zirconium oxide (ZrO2) is widely used in many kind of industries to improve the mechanical properties as well as the heat resistance of materials. However, ZrO2 nanoparticles often tend to agglomerate together, so efficiency of ZrO2 nanoparticles is not as expected. This paper presents results of modifying ZrO2 nanoparticles with polydimethyl siloxane (PDMS). The study has pointed out the optimal reaction conditions included mass ratio between ZrO2/PDMS: 1/0.5 at 200 oC. Results of FT-IR infrared spectroscopy, X-ray energy scattering spectroscopy analysis,… showed that modified ZrO2 nanoparticles were grafted siloxane on surfaces. Modified ZrO2 nanoparticles have better dispersibility in xylene than unmodified ones. Therefore, the modified ZrO2 nanoparticles can be used in paint and glue manufacturing industries well.